Activité antioxydante des extraits phénoliques de caroube - Elaoufi Manel (My University, 2014)
This study focuses on the determination of the chemical composition, the evaluation of the antioxidant activity in vitro (DPPH) and in vivo, quantitative estimation of total polyphenols (by the Folin- Ciocalteu method) and flavonoïds (the AlCl3 method) of the ethanol extract (CEE), the extract distilled water (EWC) and methanol (EMC) 70 % (v / v) (1:10 w/v) of the carob pod (Ceratonia siliqua L.) harvested in the region of Ain Témouchent. The results show that the carob pulp is rich in total sugars (48.23%) and contains a low protein (3.68), fat (0.77%) and vitamin C (1.83%). It also contains 9.69% of ash and 12.1% of moisture. The CEE was found to have the highest antioxidant activity with EC50 (0.28 mg / ml) and therefore, a significant dose-dependent anti- radical activity. These preliminary observations suggest that stronger anti- radical activity of the CEE could be related to its polyphenol content which is also higher compared to the EWC and EMC. The flavonoïd content is also higher in the CEE. Several fractions of CEE obtained by HPLC were identified by LC-MS/MS. This identification shows the presence of polyphenolic compounds, Palmitoleic acid, isoprenyl coumaric, cinnamic and its derivatives. The caffeate Prenyl was found in most fractions, while many types of flavonoids, such as Chrysin, Kaempferol, the methyl quercetin, quercetin and tectochrysine were found as well. The antioxidant activity of the ethanol extract (CEE) is confirmed in vivo in 24 Wistar rats divided into 04 treatment groups as follows: control, (G1) : 80mg/kg/jour of CEE ; (G2): 30 mg/kg/day of AlCl3, (G3): 80 mg/kg/day of CEE 30min before 30 mg/kg/day of AlCl3. The daily oral pretreatment CEE 30min before AlCl3 for 28 days resulted in a significant improvement in the total antioxidant capacity of blood indicated by the drop in glycemia and restoring lipid profile and liver and renal markers. The parameters of oxidative stress were restored by reducing lipid peroxidation and stimulation activities of SOD, CAT and glutathione peroxidase. These data suggest that the carob pulp has antioxidants effects in vitro and in vivo and may thus be proposed as a food additive to protect against damage from oxidative stress.
Keywords: Carob, polyphenols, antioxidant activity, LC-MS/MS, AlCl3